2007
DOI: 10.1111/j.1365-2141.2007.06755.x
|View full text |Cite
|
Sign up to set email alerts
|

JAK2‐V617F mutation analysis of granulocytes and platelets from patients with chronic myeloproliferative disorders: advantage of studying platelets

Abstract: SummaryThere have been conflicting reports over the JAK2-V617F mutation status of platelets in chronic myeloproliferative diseases (CMPDs). The aim of this study was to analyse JAK2-V617F status, not only in granulocytes but also in platelets. The JAK2-V617F mutation was analysed in both granulocytes and platelets in 115 patients with CMPDs using direct sequencing. JAK2-V617F was detected in granulocytes from 71 of those patients, all 71 of whom also had platelet JAK2-V617F expression. The remaining 44 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…T-cells recovered from the remaining mononuclear cells were further positively selected using anti-CD3 immunoconjugated magnetic beads (Miltenyi Biotec, Bergisch Gladbach Germany). Granulocytes were isolated from the pellet after the removal of red blood cells by hypotonic lysis (5).…”
Section: Isolation Of Platelets Granulocytes and T-cells In Vitro Cmentioning
confidence: 99%
See 1 more Smart Citation
“…T-cells recovered from the remaining mononuclear cells were further positively selected using anti-CD3 immunoconjugated magnetic beads (Miltenyi Biotec, Bergisch Gladbach Germany). Granulocytes were isolated from the pellet after the removal of red blood cells by hypotonic lysis (5).…”
Section: Isolation Of Platelets Granulocytes and T-cells In Vitro Cmentioning
confidence: 99%
“…We have previously reported the advantage of studying the JAK2-V617F mutation in platelets in MPN patients, as we have found that approximately 10% of essential thrombocythemia (ET) patients only have the JAK2-V617F mutation in their platelets (5). Based on these results, we decided to investigate the JAK2-V617F mutation status in four cell lineages of granulocytes, platelets, T-cells, and erythroid colonies, and then determine whether there was a difference in the cell lineages that are involved with the JAK2-V617F mutation in each of the MPN subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work suggested that analysis of platelets may be a more sensitive approach for detecting JAK2 V617F in BCR-ABL1-negative MPN patients as compared with analysis of granulocytes alone. 25 We suggest that examination of RNA from buffy coats (which include platelets and granulocytes) may also offer increased sensitivity when compared with looking at a single cell population. Finally, unlike many of the more sensitive published assays, our assay does not require isolation of granulocytes, because this procedure is difficult to integrate into most laboratories' workflow.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of platelet RNA may be particularly relevant for ET, because prior studies have indicated that the analysis of platelet RNA may improve the clinical sensitivity of JAK2 V617F assays. 25 Based on these considerations, we developed an assay that uses allele-specific PCR and real-time detection with hydrolysis probes for the quantification of JAK2 V617F and wild-type JAK2 transcript levels. Our initial evaluation indicates the method is sufficiently sensitive, specific, and reproducible to be used in clinical molecular pathology laboratories.…”
mentioning
confidence: 99%
“…Using a direct sequencing method we described before, the JAK2-V617F mutation status was investigated [23]. To confirm the existence of the JAK2-V617F mutation, an allele-specific polymerase chain reaction (AS-PCR) was performed as previously described [11].…”
Section: Dna Preparation and Jak2 Mutation Analysismentioning
confidence: 99%